2017
DOI: 10.1161/strokeaha.116.016368
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Symptomatic Intracranial Hemorrhage After Endovascular Treatment of Acute Ischemic Stroke

Abstract: Incidence of SICH after thrombectomy is higher in Asian patients with acute ischemic stroke. Cardioembolic stroke, poor collateral circulation, delayed endovascular treatment, multiple passes with stent retriever device, lower pretreatment Alberta Stroke Program Early Computed Tomography Score, higher baseline neutrophil ratio may increase the risk of SICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
177
8
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 258 publications
(221 citation statements)
references
References 27 publications
29
177
8
7
Order By: Relevance
“…While no association between RD and postprocedural ICH was observed in a former study of patients with anterior circulation stroke [5], further studies, evaluating a possible influence of cerebral microbleeds in these patients, would be desirable. Interestingly, we observed a strong trend toward an association between delayed groin puncture and ICH, which is in accordance to a previous study, reporting an association between symptomatic ICH and symptom-to-groin times that exceeded 270 min [21]. These findings clearly indicate the importance of starting endovascular treatments as fast as possible.…”
Section: Discussionsupporting
confidence: 92%
“…While no association between RD and postprocedural ICH was observed in a former study of patients with anterior circulation stroke [5], further studies, evaluating a possible influence of cerebral microbleeds in these patients, would be desirable. Interestingly, we observed a strong trend toward an association between delayed groin puncture and ICH, which is in accordance to a previous study, reporting an association between symptomatic ICH and symptom-to-groin times that exceeded 270 min [21]. These findings clearly indicate the importance of starting endovascular treatments as fast as possible.…”
Section: Discussionsupporting
confidence: 92%
“…Our previously published study showed that delayed endovascular treatment and multiple passes with stent retriever device may increase the risk of sICH [33]. In our study, patients in the general anesthesia group had longer door-to-puncture time than that of the conscious sedation group.…”
Section: Discussionsupporting
confidence: 45%
“…Stenting with concomitant use of antiplatelet drugs may increase the risk of sICH. Second, passes of thrombectomy (≥3 passes) was higher than that in both NASA and STAR [23]. Repeated thrombectomy may lead to intima injury and may be associated with an increased risk for sICH [24].…”
Section: Discussionmentioning
confidence: 99%